2005
DOI: 10.1118/1.1992267
|View full text |Cite
|
Sign up to set email alerts
|

Precision targeting of liver lesions using a novel electromagnetic navigation device in physiologic phantom and swine

Abstract: Radiofrequency ablation of primary and metastatic liver tumors is becoming a potential alternative to surgical resection. We propose a novel system that uses real-time electromagnetic position sensing of the needle tip to help with precision guidance into a liver tumor. The purpose of this study was to evaluate this technology in phantom and animal models. Using an electromagnetic navigation device, instrumented 18 g needles were advanced into radioopaque tumor targets in a respiratory liver phantom. The phant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 20 publications
2
51
0
Order By: Relevance
“…While tracking accuracy and robustness are critical factors, they are not sufficient for making an informed decision with regard to the utility of EMTS tracking for a specific procedure performed in a specific environment. The procedures we have targeted include radio frequency ablation ͑RFA͒ of liver tumors, 7 creation of a transjugular intrahepatic portosystemic shunt ͑TIPS͒, 8 carotid stent deployment, 9 vertebroplasty, 10 needle biopsies of liver lesions, 11 and transbronchial biopsies. 12 These procedures are performed in three different environments: an interventional radiology suite, a CT suite, and a pulmonology suite ͑Fig.…”
Section: Introductionmentioning
confidence: 99%
“…While tracking accuracy and robustness are critical factors, they are not sufficient for making an informed decision with regard to the utility of EMTS tracking for a specific procedure performed in a specific environment. The procedures we have targeted include radio frequency ablation ͑RFA͒ of liver tumors, 7 creation of a transjugular intrahepatic portosystemic shunt ͑TIPS͒, 8 carotid stent deployment, 9 vertebroplasty, 10 needle biopsies of liver lesions, 11 and transbronchial biopsies. 12 These procedures are performed in three different environments: an interventional radiology suite, a CT suite, and a pulmonology suite ͑Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Deviations in the computed liver movement can be mainly attributed to the placement of the fiducial needles which was difficult to reproduce in different livers as well as to variations in organ shape and tissue consistency. Due to the complexity of hepatic motion most groups perform animal experiments [2,8] or cadaver studies [3] for validating image-guided systems. Cleary et al [9] developed a respiratory liver motion simulator including a synthetic liver mounted on a one degree of freedom linear motion platform.…”
Section: Discussionmentioning
confidence: 99%
“…This system is intended to track the movement of the target. Banovac F et al (4) have reported the precision targeting of liver lesions, using a novel electromagnetic navigation device in a physiological phantom and in swine. It uses an electromagnetic field-sensing device that can track the position of small sensors embedded in needles or instruments.…”
Section: Introductionmentioning
confidence: 99%